Interfaces and interface conditions - Späth, Andreas (Walter de Gruyter, 2007)
Biographical note: Andreas Späth, University ofLeipzig.
Includes bibliographical references and index
Keywords: Konferenzschrift -- 2004 -- Leipzig; Performanz; Generative Grammatik